MENINGKATKAN KREATIVITAS SISWA MELALUI METODE QUANTUM LEARNING DI PASRAMAN SAHA DHARMA SARASWATI, JOGONALAN KABUPATEN KLATEN - Safira A.D, Komang Dea; Nurcahyo, Andrian Dwi; Karismayani, Made; Tusmawanto, Angki; Santoso, Apri; Suryani, Tri; Supriyanto, Agus; Santiawan, I Nyoman (UNHI Press, 2025)
Pasraman Saha Dharma Saraswati in Klaten district. pasraman which consists of several levels ranging from early childhood, kindergarten, elementary, junior high, to junior high. because students are different, when they are at the pasraman they must have some obstacles that interfere with the learning process, for example, they are often noisy during learning, ridicule each other, causing fights and many are lazy to go Community service activities through learning at the Saha Dharma Saraswati pasraman by STHD Klaten students can do well. Within a limited time, pasraman students were able to be directed to develop the values ??of Hindu Religious Education such as religious attitudes (Sradha and Bhakti), discipline, friendly and polite attitudes, tolerance, caring attitudes, and interactive attitudes. During the service period, the team used the quantum learning method such as having a question and answer session between the team and students during learning, so that the application of this method trains students to be tolerant of the opinions of their different friends. The conclusion is that the learning method used by the service team has positive implications for students, namely increasing motivation and enthusiasm of students to take part in the entire series of community service activities.